(untitled) (Al-Qamar, 2022)
Consensus (Ijmaʻ) ranks after the Quran and Sunnah among the sources of Islamic jurisprudence. Many Shariʻah rules are authenticated by the source of Ijmaʻ. This article is aimed to discuss the two primary issues relating to Ijmaʻ and to find the preferred opinion of Muslim jurists about these issues. The first issue is about the evidence for ijma’. The author has preferred this opinion that although the condition of evidence for the validation of ijma’ is not found in the early literature available on Ijmaʻ yet any ijma’ must have evidence which may integrate it with Quran and Sunnah. The second issue is about analogical reasoning and whether or not it has the capacity to perform as evidence for ijma’. The writer thinks that Qiyas has this capacity and it must be considered in this regard.